The Research Dynamics and Trends of Aesthetics, Based on ScientificKnowledge Mapping: An Analysis of the Papers Published in theBritish Journal of Aesthetics (2001-2022) and the Journal ofAesthetics and Art Criticism (2011-2022) (Asian Journal of Social Science Studies, 2022)
This paper is based on the papers published in recent 10 years (2001-2022) from The British Journal of Aesthetics and The Journal of Aesthetics and Art Criticism, both of which enjoy high reputation in the aesthetic field. This paper uses scientific knowledge mapping and draws the knowledge mapping by using CiteSpace. Guided by visualization of conclusions, it outlines some development trends of aesthetics discipline and presents the research hot spots and changes of international aesthetics from a new perspective. Then this paper discusses the characteristics of aesthetics itself.